Hydrothermal Growth of Quasi-Monocrystal ZnO Thin Films and Their Application in Ultraviolet Photodetectors. (16th June 2015) - Tu, Yung-Chun; Wang, Shui-Jinn; Lin, Tseng-Hsing; Hung, Chien-Hsiung; Tsai, Tsung-Che; Wu, Ru-Wen; Uang, Kai-Ming; Chen, Tron-Min
Abstract : Quasi-monocrystal ZnO film grown using the hydrothermal growth method is used for the fabrication of Cu2 O/ZnO heterojunction (HJ) ultraviolet photodetectors (UV-PDs). The HJ was formed via the sputtering deposition of p-type Cu2 O onto hydrothermally grown ZnO film (HTG-ZnO-film). The effect of annealing temperature in the nitrogen ambient on the photoluminescence spectra of the synthesized ZnO film was studied. The optoelectronic properties of Cu2 O/ZnO film with various Cu2 O thicknesses (250–750 nm) under UV light (365 nm; intensity: 3 mW/cm 2 ) were determined. The UV sensitivity of the HTG-ZnO-film-based UV-PDs and the sputtered ZnO-film-based UV-PDs were 55.6-fold (S HTG ) and 8.8-fold (S sputter ), respectively. The significant gain in sensitivity (S HTG / S sputter = 630%) of the proposed ZnO-film-based device compared to that for the device based on sputtered film can be attributed to the improved photoelectric properties of quasi-monocrystal ZnO film.